Analisis SWOT Pariwisata di Kelurahan 2 Ulu Kota Palembang - Abdurrahman Arif; Lisdiana Lisdiana; Ivana Ivana; Diany Putri Partiwi Saladin; Jusnita Sari (Jurnal Kemitraan Masyarakat, 2025)
The construction of the Musi 6 Bridge in 2 Ulu Village is an opportunity to develop existing potential. One of them is tourism development. A number of tourist attractions have the potential for development as an effort for sustainable tourism. For this reason, Community Service conducted a SWOT analysis of tourism and recommendations that are relevant to the situation in the field. Approaching the Community through interviews and Focus Group Discussions is a method of data analysis. In general, tourism in the 2 Ulu Area requires Community skills in activity management because the available locations can be used as a means of performance or exhibition. Of course, this is a collaboration between the surrounding community, government, private sector and community.